Efek Penurunan Gula Darah Ekstrak Etanol Daunkaramunting (Rhodomyrtus Tomentosa (Ait.) Hassk.) Metode Toleransi Glukosa - Mevy Trisna; Rahmita Yoliana (Journal Pharma Saintika, 2023)
Research on "Test the blood sugar lowering effect of the ethanol extract of karamunting leaves (Rhodomyrtus tomentosa (ait.) Hassk.) Using the glucose tolerance method on male white mice" was carried out orally by measuring the blood sugar levels of mice every 30 minutes for 2 hours with doses of 3, 2mg, 1.6mg, and 0.8mg. The results of the study using the oral glucose tolerance test method showed that the effect of glucose tolerance from karamunting leaf extract at a dose of 3.2mg/20gBB averaged blood sugar levels after administration of 50% glucose from 294 mg/dl to 123mg/dl, a dose of 1.6mg/dl. 20gBB average blood sugar level after administration of glucose 50% from 269.33 mg/dl to 133.67 mg/dl, 0.8mg/20gBB average blood sugar level after administration of glucose 50% from 261.67mg/dl to 135mg/dl. From the data analysis carried out, it was found that the data were normally distributed and there was a homogeneous variance with a significant level = 0.05 and continued with a one-way anava test where  Fhitung 3.63 ≤ Ftabel 4.07 which means there is no significant difference in the extract group karamunting leaf ethanol (Rhodomyrtus tomentosa (Ait.) Hassk.) It can be concluded that karamunting leaf ethanol extract is efficacious as an antidiabetic.